Reward, motivation and brain imaging in human healthy participants – A narrative review - Weinstein, Aviv M. (Frontiers in Behavioral Neuroscience, 2023)
Over the past twenty years there has been an increasing number of brain imaging studies on the mechanisms underlying reward motivation in humans. This narrative review describes studies on the neural mechanisms associated with reward motivation and their relationships with cognitive function in healthy human participants. The brain’s meso-limbic dopamine reward circuitry in humans is known to control reward-motivated behavior in humans. The medial and lateral Pre-Frontal Cortex (PFC) integrate motivation and cognitive control during decision-making and the dorsolateral PFC (dlPFC) integrates and transmits signals of reward to the mesolimbic and meso-cortical dopamine circuits and initiates motivated behavior. The thalamus and insula influence incentive processing in humans and the motor system plays a role in response to action control. There are reciprocal relationships between reward motivation, learning, memory, imagery, working memory and attention. The most common method of assessing reward motivation is the Monetary Incentive Delay Task (DMRT) and there are several meta-analyses of this paradigm. Genetics modulates motivation reward, and dopamine provides the basis for the interaction between motivational and cognitive control. There is some evidence that male adolescents take more risky decisions than female adolescents and that the lateralization of reward-related DA release in the ventral striatum is confined to men. These studies have implications for our understanding of natural reward and psychiatric conditions like addiction, depression and ADHD. Furthermore, the association between reward and memory can help develop treatment techniques for drug addiction that interfere with consolidation of memory. Finally, there is a lack of research on reward motivation, genetics and sex differences and this can improve our understanding of the relationships between reward, motivation and the brain.